DOI: 10.1007/978-3-540-74549-5_19
|View full text |Cite
|
Sign up to set email alerts
|

Fusion of Near Infrared Face and Iris Biometrics

Abstract: In this paper, we present a method for fusing face and iris biometrics using single near infrared (NIR) image. Fusion of NIR face and iris modalities is a natural way of doing multi-model biometrics because they can be acquired in a single image. An NIR face image is taken using a high resolution NIR camera. Face and iris are segmented from the same NIR image. Face and iris features are then extracted from the segmented parts. Matching of face and iris is done using the respective features. The matching scores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…For classification purposes, WPNN classifier is used where features of face and iris are feed to make the final decision of whether the claimed user is truly accepted or rejected. A score level fusion of near infrared face and iris was addressed by Zhang et al [18] in 2007 the proposed framework was tested using different combination rule and it is found that on a close set the genuine accept rate (GAR) of face and two irises increase from 97.35% to 99.75% and on an open set it is increased from 83.31% to 98.12% when FAR is at 0.001.In 2008, Morizet et al [24] present a novel approach for face and iris based on a precise statistical analysis of bootstrapped match scores generated from similarity matrices. The overall performance of the biometric system depends on the separation between genuine and imposter distribution, to boost the exhibition of the framework the separation must be expanded.…”
Section: Related Workmentioning
confidence: 99%
“…For classification purposes, WPNN classifier is used where features of face and iris are feed to make the final decision of whether the claimed user is truly accepted or rejected. A score level fusion of near infrared face and iris was addressed by Zhang et al [18] in 2007 the proposed framework was tested using different combination rule and it is found that on a close set the genuine accept rate (GAR) of face and two irises increase from 97.35% to 99.75% and on an open set it is increased from 83.31% to 98.12% when FAR is at 0.001.In 2008, Morizet et al [24] present a novel approach for face and iris based on a precise statistical analysis of bootstrapped match scores generated from similarity matrices. The overall performance of the biometric system depends on the separation between genuine and imposter distribution, to boost the exhibition of the framework the separation must be expanded.…”
Section: Related Workmentioning
confidence: 99%
“…There are no free available multimodal databases which combine face and iris modalities of the same person (real-user). However, in most of the recent fusion studies [10,22,23,27] on face and iris biometrics, experiments are carried out on independent face and iris databases which result in the creation of chimeric users (the virtual subjects created with biometric traits of different users) [38]. To validate the performance of algorithms and fusion methods in our multimodal biometric system, a multimodal biometric database using the ORL face database [39] and the CASIA iris database [40] is constructed.…”
Section: A Databasementioning
confidence: 99%
“…It has been investigated in many existing works and it was proved that there is a substantial impact on the overall system performance by considering the performance metrics of the fusion level. In [3] the signal level fusion operation is performed to combine the iris and face images and the scores are assigned to formulate the composite images and finally normalized using a min-max rule to optimize the modality. In [6] Log-Gabor transformations driven feature level coding for template creations and particle swarm optimization (PSO) is used for feature selection to minimize the redundant information during template creation.…”
Section: Related Workmentioning
confidence: 99%